Parental Alienation: Conception and Effects from Islamic Educational Perspective - Alshboul, Asma; Alrefaie, Sameera; Alshboul, Ruba (Jordan Journal of Islamic Studies, 2024)
The current study aimed to clarify the concept of paternal alienation and its effects from an Islamic educational perspective. It utilized both inductive and deductive methodologies to achieve its objectives. The study reached several conclusions, the most notable being that paternal alienation is defined as the prolonged absence of a father from the family, preventing him from directly fulfilling his parental responsibilities due to reasons such as travel or other obligations. Key terms related to paternal alienation include parental deprivation and fatherly void. The effects of paternal alienation on the family are categorized into four areas: those impacting the mother, the father, those affecting both parents, and those related to the children. Based on these conclusions, the study recommends raising awareness among mothers who are solely responsible for their children, encouraging them to strengthen their bond with their children to help compensate for the father’s absence.